Legal & Intellectual Property Dimension of Health & Access to Medicines in India - M.Z.M. Nomani1, Alaa K.K.Alhalboosi2, Mohammad Rauf3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Trade- Related Aspects of Intellectual Property Rights (TRIPS) Agreement, 1995 established synergy with human rights laws in realization of right to health, access to medicine and sustainable development. The Doha Declaration on Public Health, 2001; Sustainable Development Goals, 2015-2030 and United Nations Secretary- General’s High- Level Panel on Access to Medicines Report, 2016 promote innovation of health technologies in developing countries. It is estimated that 75 per cent of the world’s population is health deficient and medicine starved due to patenting requirement of pharmaceutical industries. India passed Patents (Amendment) Act, 2005 dealing with exclusive marketing right, product patent and process patent to protect the interest of the generic drugs in compliance of TRIPS Agreement, 1995 under public interest. In post Patents (Amendment) Act, 2005 phase India faced formidable challenge of the Swiss drug maker Novartis’ patent application for Gleevec in Madras High Court, 2006; Intellectual Property Appellate Board (IPAB) in 2009 and Supreme Court in 2013. The judicial exuberance struck a balance between patent right, health right and access to medicine in Indian socio-economic context. It is followed by spelling out of the National Intellectual Property Right (IPR) Policy, 2016 focused on enhancing access to healthcare as human right.